2023
DOI: 10.1073/pnas.2300463120
|View full text |Cite
|
Sign up to set email alerts
|

Utility-value intervention promotes persistence and diversity in STEM

Abstract: We tested the long-term effects of a utility-value intervention administered in a gateway chemistry course, with the goal of promoting persistence and diversity in STEM. In a randomized controlled trial (N = 2,505), students wrote three essays about course content and its personal relevance or three control essays. The intervention significantly improved STEM persistence overall (74% vs. 70% were STEM majors 2.5 y later). Effects were larger for students from marginalized and underrepresented racial/ethnic gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…Techniques to improve time management appear in the psychology research literature and involve training to promote prioritizing, goal setting, strategizing, and monitoring; these studies were not performed within a classroom setting so future work would need to adapt and evaluate these techniques within instruction. Techniques have also been found to improve chemistry students’ motivation including the use of active learning techniques, teaching chemistry in context, or prompting students to write on the utility of the topics learned. , The current results suggest that interventions to improve chemistry students’ motivation or time management may address these individual challenges and improve student success.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Techniques to improve time management appear in the psychology research literature and involve training to promote prioritizing, goal setting, strategizing, and monitoring; these studies were not performed within a classroom setting so future work would need to adapt and evaluate these techniques within instruction. Techniques have also been found to improve chemistry students’ motivation including the use of active learning techniques, teaching chemistry in context, or prompting students to write on the utility of the topics learned. , The current results suggest that interventions to improve chemistry students’ motivation or time management may address these individual challenges and improve student success.…”
Section: Discussionmentioning
confidence: 72%
“…Techniques have also been found to improve chemistry students' motivation including the use of active learning techniques, 27 teaching chemistry in context, 28 or prompting students to write on the utility of the topics learned. 20,29 The current results suggest that interventions to improve chemistry students' motivation or time management may address these individual challenges and improve student success.…”
Section: ■ Discussionmentioning
confidence: 83%
“…This suggests that the UVIs might have broader effects that extend beyond the chemistry class, with implications for persistence in STEM. In fact, a follow-up study found that URM students in Study 2 were 14 percentage points more likely to remain in a STEM major two and a half years later if they were in the UVI condition, relative to those in the control group (Asher et al, 2023). Moreover, this direct intervention effect on persistence was partially mediated by the future plans variable, providing strong evidence for the importance of motivational processes in UVI dynamics and understanding persistence in the STEM pipeline.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, the UVI stimulates all of these processes, and the effects on the future planning variables in Studies 2 and 3 (career/degree plans and deeper involvement) are two markers of the significance of UVIs for future consequences (Asher et al, 2023). Furthermore, in Study 3, we found the first evidence that a UVI implemented in one course (introductory chemistry) can have positive effects on performance in a second gateway course (introductory biology).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation